2010
DOI: 10.3390/cancers20100043
|View full text |Cite
|
Sign up to set email alerts
|

Regional Therapy for Recurrent Metastatic Melanoma Confined to the Extremity: Hyperthermic Isolated Limb Perfusion vs. Isolated Limb Infusion

Abstract: Melanoma patients with recurrent disease confined to an extremity can be offered one of two regional therapies that both give high complete response rates. Isolated limb infusion (ILI) is a newer technique performed with catheters and tourniquets that has a reduced potential morbidity, decreased efficacy and does not treat the regional nodal basin. Hyperthermic Isolated Limb Perfusion (HILP) is an open surgical technique that includes removal of the regional nodal basin as part of the surgical procedure. An an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…29 However, we have demonstrated that Esmarch tourniquets can be utilized very effectively in ILI as an alternative to a pneumatic tourniquet to achieve a higher level of isolation. 23 In addition, we have safely performed nodal dissections in conjunction with an ILI after completing the regional treatment and correcting the patient’s coagulation status by reversing the heparinization with protamine.…”
Section: Discussionmentioning
confidence: 90%
“…29 However, we have demonstrated that Esmarch tourniquets can be utilized very effectively in ILI as an alternative to a pneumatic tourniquet to achieve a higher level of isolation. 23 In addition, we have safely performed nodal dissections in conjunction with an ILI after completing the regional treatment and correcting the patient’s coagulation status by reversing the heparinization with protamine.…”
Section: Discussionmentioning
confidence: 90%
“…168,169 ILI is associated with lower rates of toxicity and morbidity compared with ILP, but retrospective comparisons of response and survival with ILP versus ILI have shown varying results. 168,[170][171][172][173][174] An analysis of 7 studies involving 576 patients, primarily with stage III disease and treated with melphalan/actinomycin D combination via ILI, showed an overall response rate of 73%, with complete response in 33% (range, 26%-44% across studies), partial response in 40% (33%-53%), and stable disease in 14%. 167 A smaller pooled analysis of 2 additional studies (N=58), one a noncomparative phase II study (ClinicalTrials.gov identifier: NCT00004250), showed similar overall response rates for stage IIIB versus stage IIIC disease (48% vs 40%), and similar 5-year survival rates (38% vs 52%).…”
Section: Regional Therapy: Isolated Limb Perfusion and Infusionmentioning
confidence: 99%
“…This therapy is technically challenging, requiring general anesthesia and an oxygenated extracorporeal cardiopulmonary bypass system. HILP has an ORR of 77% and is associated with moderate rates of postprocedure complications . A large phase III multicenter randomized study comparing adjuvant HILP in patients with resected high‐risk primary melanoma demonstrated a trend towards improved disease‐free survival although no significant benefit in OS corroborated in other studies .…”
Section: Discussionmentioning
confidence: 94%
“…Table summarizes the key data for each modality and presents the pooled results including the weighted ORR and meta‐analysis data. Assessed studies included: randomized controlled trials, nonrandomized phase I and II comparative and noncomparative studies, and prospective or retrospective case series (NHMRC levels II–IV evidence; Tables S2‐S9) . Only two therapies: amputation and topical imiquimod, were suitable for formal meta‐analysis ( I 2 value ≤ 40%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation